The “social life” of rural tourism state policies in Argentina - Pérez Winter, Cecilia (Universidad Nacional del Litoral, 2021)
In this article we are interested in discussing public policies as dynamic processes; especially those related with rural tourism development. In Argentina these types of policies were created during 1990s and the National Institute of Agricultural Technology/INTA was one of the pioneering state agencies in the field. Hence, we propose to examine: i) the political-economic context in which these policies aroused and developed; ii) the actors who participated; iii) the characteristics and strategies that were configured and implemented; and iv) tensions that emerged and expressed during the process. We identify and examine three relevant actions/strategies that lead to the consolidation of rural tourism policies at INTA: the first experiences developed in Patagonia and Santa Fe province; the formation of a centralized working team in the National Coordination of Transfer and Extension in Buenos Aires and the institutional adoption of territorial development approach.